Platelets and Fibrinogen: Emerging Complexity in Trauma-Induced Coagulopathy - John, Alexander E.; White, Nathan J. (Seminars in Thrombosis and Hemostasis, 2020)
Trauma induces a change in nearly every observable aspect of hemostasis, generally tipping the balance toward trauma-induced coagulopathy (TIC) and bleeding in the critical early stages. Two particularly important aspects of TIC are platelets and fibrinogen, which are the primary determinants of clot formation and hemostasis. Their loss and dysfunction represent important transition points between coagulopathy phenotypes, highlighting their mechanistic roles in TIC as well as unveiling new potential avenues toward important diagnostic and therapeutic interventions. This review synthesizes current knowledge of platelets and fibrinogen during TIC, with a focus on emerging concepts related to their dysfunction and development of new therapeutic approaches.
Keywords: trauma; coagulopathy; platelets; fibrinogen